LITERASI DIGITAL SEBAGAI UPAYA MENCEGAH PENYEBARAN HOAX - Ajeng Cahya Lestari; Alyaa Mahira, Annisa Khurrotul Luthfil Aini, Chyntia Martini, Nadia Karin, Rijal Abdillah (ADISAM PUBLISHER, 2025)
The spread of hoaxes in the digital era is a serious challenge that affects society, especially students as active users of social media. This study aims to improve the digital literacy of Bhayangkara University students in Greater Jakarta to prevent the negative impact of hoaxes. This social intervention program uses a psychoeducational method that includes counseling, interactive discussions, and evaluation using a questionnaire. The results showed that good digital literacy can help students recognize false information, verify the truth of information, and reduce the spread of hoaxes. This intervention has a positive impact on changing maladaptive behavior into adaptive. This study recommends a sustainable and more interactive digital literacy program to expand its positive impact in the community